Zambia - Public Expenditure Review : Public Expenditure, Growth and Poverty - A Synthesis - World Bank (Washington, DC, 2013)
At the heart of the growth problem, the persistence of poverty, and issues of policy reform in Zambia is the public sector reform program. The best practice in public sector reform identifies three areas in which governments can improve their performance and their impact on the economy and poor: 1) macroeconomic discipline (the satabilization problem); 2) strategic priority setting (the allocation problem); and 3) efficient public-service delivery (the execution problem). Zambia's problem appears to be in all three areas. In particular, the aggregate performance, allocation, and execution of the budget are vital to the success of Zambia's public sector reform program. All three areas, particularly the allocation and execution issues, as they apply to public expenditure are the subject matter of the present public expenditure review (PER).